The Effectiveness of Corporate Social Responsibility (CSR) as a Corporate Communication Strategy - Kharisma Citra; Antonius Antonius; Jonathan Napitupulu (Green Publisher Indonesia, 2025)
This study investigates the effectiveness of Corporate Social Responsibility (CSR) as a corporate communication strategy by conducting a structured literature review of recent academic sources. The analysis categorizes the literature into key themes such as CSR’s impact on corporate image, stakeholder engagement, the role of social media, ethical concerns, and measurement of communication effectiveness. Findings reveal that CSR, when strategically communicated, enhances corporate reputation, builds stakeholder trust, and can lead to improved organizational performance. However, the effectiveness of CSR communication depends on several factors, including message framing, emotional appeal, platform selection, and industry context. Studies also emphasize the growing importance of participatory and dialogic communication approaches, particularly in digital environments, where consumers value authenticity and interaction. Furthermore, the credibility of CSR messaging and alignment between communicated motives and actual corporate actions are critical to avoiding stakeholder skepticism. The review highlights that while CSR communication offers significant strategic benefits, it also poses reputational risks if perceived as inauthentic or excessive. This study contributes to the understanding of CSR as a multidimensional tool in corporate communication and underscores the need for an integrated, stakeholder-focused communication strategy grounded in transparency, relevance, and ethical intent.